Pengaruh Ketepatan Waktu, Fasilitas dan Harga Tiket Terhadap Kepuasan Penumpang Kereta Api: (Studi Pada KA. Joglosemarkerto Semarang Tawang – Solo) - Dian Novanti Rahmasari; Triyono Triyono (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
PT. KAI is an abbreviation of PT. Kereta Api Indonesia, this company is in the form of a company or Persero business entity and is the only type of business engaged in the field of transportation services, both passenger and freight transport and is under state ownership or a State-Owned Enterprise (BUMN). PT. Kereta Api Indonesia realizes that the role of Railways, especially in terms of service, must be balanced with the level of passenger needs. This study aims to test the hypothesis whether Punctuality, Facilities, and Ticket Prices affect Passenger Satisfaction of the Joglosemarkerto Semarang Tawang – Solo Train. The population in this study was 1200 people while the sample was calculated using the Slovin formula of 100 respondents. The sampling technique was carried out by accidental sampling technique. Data analysis was performed using multiple linear regression analysis. The results showed that the independent variables consisting of Punctuality, Facilities and Ticket Prices had a positive and significant effect on Passenger Satisfaction